(untitled) (Research, Society and Development, 2024)
The article presents an analysis of inclusive education in the teaching of Science and Biology, historically contextualizing the development of inclusive education in Brazil and internationally, highlighting milestones such as the creation of institutions for people with disabilities and the influence of documents such as the Universal Declaration of Human Rights and the Law of Guidelines and Bases of National Education. The study emphasizes the importance of active participation of students in the learning process, with an emphasis on teacher training as a key element in promoting inclusive education. The methodology adopted involves a qualitative bibliographic review, with the objective of searching for articles related to the training of Science/Biology teachers from the perspective of inclusive education. The results and discussion highlight the importance of Science and Biology subjects in the school curriculum and the need to adapt teaching practices to meet the individual needs of students, especially those with disabilities. Challenges faced by educators are addressed, such as the lack of initial training in inclusive education and the scarcity of adequate teaching resources. Continuous teacher training is highlighted as essential to overcome these obstacles and promote more effective and inclusive pedagogical practice. The research also highlights the political dimension of education and the importance of promoting comprehensive and ongoing debates on school inclusion. In short, the article emphasizes the urgency of adopting inclusive and adaptive approaches to ensure quality education for all, recognizing the need for collective efforts to achieve this goal.